Zooming in on Butyrate-Producing Clostridial Consortia in the Fermented Grains of Baijiu via Gene Sequence-Guided Microbial Isolation - Chai, Li-Juan; Lu, Zhen-Ming; Zhang, Xiao-Juan; Ma, Jian; Xu, Peng-Xiang; Qian, Wei; Xiao, Chen; Wang, Song-Tao; Shen, Cai-Hong; Shi, Jin-Song; Zheng-Hong, Xu (Frontiers in Microbiology, 2019)
Butyrate, one of the key aroma compounds in Luzhou-flavor baijiu, is synthesized through two alternative pathways: butyrate kinase (buk) and butyryl-CoA:acetate CoA-transferase (but). A lack of knowledge of butyrate-producing microorganisms hinder our ability to understand the flavor formation mechanism of baijiu. Here, temporal dynamics of microbial metabolic profiling in fermented grains (FG) was explored via PICRUSt based on 16S rRNA gene sequences. We found Bacilli and Bacteroidia were the major potential butyrate producers in buk pathway at the beginning of fermentation, while later Clostridia dominated the two pathways. Clone library analysis also revealed Clostridia (~73% OTUs) was predominant in buk pathway throughout fermentation, followed by Bacilli and Bacteroidia, and but pathway was merely possessed by Clostridia. Afterwards, Clostridia specific-16S rRNA gene sequencing demonstrated Clostridium might be the major butyrate-producing genus in the two pathways, which was subsequently evaluated using culture approach. Seventeen Clostridium species were isolated from FG based on 16S rRNA gene sequence-guided medium prediction method. Profiles of short-chain fatty acids and but and buk genes in these species demonstrated phylogenetic and functional diversities of butyrate-producing Clostridium in FG. These findings add to illustrate the diversity of potential butyrate producers during brewing and provide a workflow for targeting functional microbes in complex microbial community.